2014
DOI: 10.1093/neuonc/not304
|View full text |Cite
|
Sign up to set email alerts
|

Integrating diffusion kurtosis imaging, dynamic susceptibility-weighted contrast-enhanced MRI, and short echo time chemical shift imaging for grading gliomas

Abstract: Combining information from DKI, DSC-MRI, and CSI increases diagnostic accuracy to differentiate low- from high-grade gliomas, possibly providing diagnosis for the individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 37 publications
5
64
0
2
Order By: Relevance
“…The present results are also comparable to a standard-dose prospective DSC perfusion study, where the authors reported a sensitivity of 78% and specificity of 91%. 29 In another DSC study, a sensitivity of 100% and specificity of 94.4% in differentiating low-and highgrade gliomas was reported. 34 In one of the patients in the present study, the tumour was reported to be low-grade based on rCBV values but turned out to be high grade at histopathology.…”
Section: Discussionmentioning
confidence: 95%
“…The present results are also comparable to a standard-dose prospective DSC perfusion study, where the authors reported a sensitivity of 78% and specificity of 91%. 29 In another DSC study, a sensitivity of 100% and specificity of 94.4% in differentiating low-and highgrade gliomas was reported. 34 In one of the patients in the present study, the tumour was reported to be low-grade based on rCBV values but turned out to be high grade at histopathology.…”
Section: Discussionmentioning
confidence: 95%
“…van Cauter et al . showed a high accuracy for the distinction of HGGs from the low-grade gliomas (LGGs) based on mean axial and radial kurtosis values 5,6 . Mean kurtosis has outperformed diagnostically the remainder of the diffusion metrics for grading (WHO grade 2–4) and predicting Ki-67 as a measure of cellularity 7 .…”
Section: Introductionmentioning
confidence: 99%
“…For comparison between DWI, DTI, and DKI, see Table 1. Several recent studies demonstrate that DKI in general has even higher accuracy as compared to DTI in various diseases including brain neoplasm [20,21], stroke [3,22,23], or neurodegenerative disorders [24][25][26][27][28]. This added diagnostic accuracy however has the price of longer acquisition times, which may among other problems increase head motion artifacts in patients.…”
Section: Diffusion Imagingmentioning
confidence: 99%